The Organic Complexation of Iron in the Marine Environment: A Review - Gledhill, Martha; Buck, Kristen N. (Frontiers in Microbiology, 2012)
Iron (Fe) is an essential micronutrient for marine organisms, and it is now well established that low Fe availability controls phytoplankton productivity, community structure and ecosystem functioning in vast regions of the global ocean. The biogeochemical cycle of Fe involves complex interactions between lithogenic inputs (atmospheric, continental or hydrothermal), dissolution, precipitation, scavenging, biological uptake, remineralisation and sedimentation processes. Each of these aspects of Fe biogeochemical cycling is likely influenced by organic Fe-binding ligands, which complex more than 99% of dissolved Fe. In this review we consider recent advances in our knowledge of Fe complexation in the marine environment and their implications for the biogeochemistry of Fe in the ocean. We also highlight the importance of constraining the dissolved Fe concentration value used in interpreting voltammetric titration data for the determination of Fe speciation. Within the published Fe speciation data, there appear to be important temporal and spatial variations in Fe-binding ligand concentrations and their conditional stability constants in the marine environment. Excess ligand concentrations, particularly in the truly soluble size fraction, seem to be consistently higher in the upper water column, and especially in Fe-limited, but productive, waters. Evidence is accumulating for an association of Fe with both small, well-defined ligands, such as siderophores, as well as with larger, macromolecular complexes like humic substances, exopolymeric substances and transparent exopolymers. The diverse size spectrum and chemical nature of Fe-ligand complexes corresponds to a change in kinetic inertness which will have a consequent impact on biological availability. However, much work is still to be done in coupling voltammetry, mass spectrometry techniques and process studies to better characterize the nature and cycling of Fe-binding ligands in the marine environment.